2016
DOI: 10.1093/nar/gkw911
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing human ADAR2 for RNA repair – Recoding a PINK1 mutation rescues mitophagy

Abstract: Site-directed A-to-I RNA editing is a technology for re-programming genetic information at the RNA-level. We describe here the first design of genetically encodable guideRNAs that enable the re-addressing of human ADAR2 toward specific sites in user-defined mRNA targets. Up to 65% editing yield has been achieved in cell culture for the recoding of a premature Stop codon (UAG) into tryptophan (UIG). In the targeted gene, editing was very specific. We applied the technology to recode a recessive loss-of-function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 56 publications
2
113
0
2
Order By: Relevance
“…A guide RNA with double BoxB-ƛ hairpins guides ADAR2 DD to edit sites encoded in the guide RNA (25). The second design utilizes full-length ADAR2 (ADAR2) and a guide RNA with a hairpin that the double strand RNA binding domains (dsRBDs) of ADAR2 recognize (23, 26). We analyzed the editing efficiency of these two systems compared to REPAIRv1 and found that the BoxB-ADAR2 and full-length ADAR2 systems demonstrated 50% and 34.5% editing rates, respectively, compared to the 89% editing rate achieved by REPAIRv1 (fig.…”
Section: Transcriptome-wide Specificity Of Repairv1mentioning
confidence: 99%
“…A guide RNA with double BoxB-ƛ hairpins guides ADAR2 DD to edit sites encoded in the guide RNA (25). The second design utilizes full-length ADAR2 (ADAR2) and a guide RNA with a hairpin that the double strand RNA binding domains (dsRBDs) of ADAR2 recognize (23, 26). We analyzed the editing efficiency of these two systems compared to REPAIRv1 and found that the BoxB-ADAR2 and full-length ADAR2 systems demonstrated 50% and 34.5% editing rates, respectively, compared to the 89% editing rate achieved by REPAIRv1 (fig.…”
Section: Transcriptome-wide Specificity Of Repairv1mentioning
confidence: 99%
“…For example, heterologous expression in Xenopus oocytes of an Editase system repaired a chloride channel mutation underlying cystic fibrosis [15]. More recently, recoding of a pathogenic mutation in PINK1, associated with Parkinson's disease, was achieved by full-length ADAR2-mediated editing in HeLa cells [47] and A-to-I and C-to-U recoding of 11 endogenous genes was achieved using an ADAR2-Cas13-guided system in HEK-293 cells [17,48]. The first demonstration of in vivo RNA editing was published recently using G>A mutant mouse models of Duchenne muscular dystrophy and ornithine transcarbamylase deficiency [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several systems were recently developed to recruit ADAR enzymes to specific sites for site-directed RNA editing [23][24][25][26][27][28][29] , providing novel tools to study biological function and a safer and reversible alternative to gene therapy 23,[47][48][49] . These RNA engineering approaches use antisense RNA oligoribonucleotides as guide RNAs (gRNAs) to recruit either engineered or endogenous ADAR enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive models derived through systematic mutagenesis would not only promote our understanding of the most prevalent type of RNA editing, but would also greatly advance the emerging field of ADAR-mediated transcriptome engineering, by informing the design of antisense RNA guides for therapeutic RNA editing. Prototypes of ADAR RNA guides were recently demonstrated to enable programmable RNA editing by forming dsRNA with target sites and recruiting endogenous ADAR proteins [23][24][25][26][27][28][29] . Improving the specificity and efficiency of programmable editing through rational design of guide/target duplexes will be critical as this new technology continues to be developed for clinical applications.…”
Section: Introductionmentioning
confidence: 99%